Harnessing the Power of the Criminal Corpse - Tarlow, Sarah (Palgrave Historical Studies in the Criminal Corpse and its Afterlife, 2018)
This open access book is the culmination of many years of research on what happened to the bodies of executed criminals in the past. Focusing on the eighteenth and nineteenth centuries, it looks at the consequences of the 1752 Murder Act. These criminal bodies had a crucial role in the history of medicine, and the history of crime, and great symbolic resonance in literature and popular culture. Starting with a consideration of the criminal corpse in the medieval and early modern periods, chapters go on to review the histories of criminal justice, of medical history and of gibbeting under the Murder Act, and ends with some discussion of the afterlives of the corpse, in literature, folklore and in contemporary medical ethics. Using sophisticated insights from cultural history, archaeology, literature, philosophy and ethics as well as medical and crime history, this book is a uniquely interdisciplinary take on a fascinating historical phenomenon.